Expression of the cannabinoid CB1 receptor in the gymnotiform fish brain and its implications for the organization of the teleost pallium. Issue 4 (22nd January 2013) - Harvey‐Girard, Erik; Giassi, Ana C.C.; Ellis, William; Maler, Leonard
Abstract Cannabinoid CB1 receptors (CB1R) are widely distributed in the brains of many vertebrates, but whether their functions are conserved is unknown. The weakly electric fish, Apteronotus leptorhynchus (Apt), has been well studied for its brain structure, behavior, sensory processing, and learning and memory. It therefore offers an attractive model for comparative studies of CB1R functions. We sequenced partial AptCB1R mRNAs and performed in situ hybridization to localize its expression. Partial AptCB1R protein sequence was highly conserved to zebrafish (90.7%) and mouse (81.9%) orthologs. AptCB1R mRNA was highly expressed in the telencephalon. Subpallial neurons (dorsal, central, intermediate regions and part of the ventral region, Vd/Vc/Vi, and Vv) expressed high levels of AptCB1R transcript. The central region of dorsocentral telencephalon (DCcore) strongly expressed CB1R mRNA; cells in DCcore project to midbrain regions involved in electrosensory/visual function. The lateral and rostral regions of DC surrounding DCcore (DCshell) lack AptCB1R mRNA. The rostral division of the dorsomedial telencephalon (DM1) highly expresses AptCB1R mRNA. In dorsolateral division (DL) AptCB1R mRNA was expressed in a gradient that declined in a rostrocaudal manner. In diencephalon, AptCB1R RNA probe weakly stained the central‐posterior (CP) and prepacemaker (PPn) nuclei. In mesencephalon, AptCB1R mRNA is expressed in deep layers of the dorsal (electrosensory) torus semicircularis (TSd). In hindbrain, AptCB1R RNA probe weakly labeled inhibitory interneurons in the electrosensory lateral line lobe (ELL). Unlike mammals, only few cerebellar granule cells expressed AptCB1R transcripts and these were located in the center of eminentia granularis pars posterior (EGp), a cerebellar region involved in feedback to ELL. J. Comp. Neurol. 521:949–975, 2013. © 2012 Wiley Periodicals, Inc.